Event‐triggered H∞ synchronization control for switched master‐slave systems subject to stochastic cyber attacks and quantization. (6th January 2020) - Li, Xianling; Liu, Ziyang; Qiu, Zhiqiang; Qi, Yiwen; Yuan, Shuo
Summary: This paper studies the event‐triggered H ∞ control for synchronization of networked switched master‐slave systems under external disturbance, stochastic attacks, and quantization. With the proposed event‐triggering schemes, the communication frequency and data packets can be effectively regulated and reduced. To reduce further the burden of network transmission, the quantized control is applied. Moreover, the network transmission delay and the stochastic cyberattacks are concerned. In addition, the synchronization problem between switched master systems and switched slave systems is transformed into a stability problem of switched error systems. By adopting multiple Lyapunov functions and average dwell time method, sufficient conditions are constructed to assure the mean‐square exponential stability with H ∞ performance of the switched error systems. Meanwhile, the stagger between data switching instants and triggering instants is discussed in the system in detail. Accordingly, the controller gains and event‐triggering parameters are obtained utilizing a set of linear matrix inequalities. Finally, a numerical simulation and a practical example are illustrated to demonstrate the effectiveness of the presented method.